Developing Students’ Speaking Competency Through Role Play - Tini Mogea (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
The purpose of this study is to develop students’ speaking competency through role play. This research is quantitative research through a pre-experimental design with a one-group pretest-posttest design. The population of this research is students of the English Department at FBS Unima, and the sample is the first semester, which consists of 25 students. The instrument of this research is a test; there are two pre- and post-tests. It is in the form of an oral test. The items in the test are constructed based on the instructional materials given to the students. The test will be given to evaluate the students’ achievement. The result shows that there is a significant improvement in students’ speaking ability through role-play technique, as shown by the scores they get. In the pre-test, the highest score is six (6) achieved by twelve students, six (5) achieved by ten (18) students, and the lowest score is five (4) achieved by three (3) students. The mean score of the pre-test is 5.20. While in the post-test, the highest score is nine (9) achieved by four (4) students, eight (8) achieved by eleven (11) students, seven (7) achieved by nine (9) students, and the lowest score is six (6) achieved by one student. The mean score of the post-test is 7.36.